Antileishmanial activity of sulphonamide nanoemulsions targeting the β-carbonic anhydrase from Leishmania species - Verônica da Silva Cardoso; Alane Beatriz Vermelho; Eduardo Ricci Junior; Igor Almeida Rodrigues; Ana Maria Mazotto; Claudiu T. Supuran (Taylor & Francis Group, 2018)
The β-carbonic anhydrase (CA, EC 4.2.1.1) from Leishmania spp. (LdcCA) is effectively inhibited by aromatic/heterocyclic sulphonamides, in the low nanomolar range, but no in vitro antileishmanial activity was detected for such compounds. We formulated some of these sulphonamides as nanoemulsions (NEs) in clove oil, and tested them in vitro against Leishmania infantum MHOM/BR/1974/PP75 and Leishmania amazonensis IFLA/BR/1967/PH8 strains. Interesting inhibitory concentrations IC50 were observed for some of the sulphonamides NEs, with IC50 as low as 3.90 µM (NE-3F) and 2.24 µM (NE-5B) for L. amazonensis and 3.47 µM (NE-5B) for L. infantum. Some of the investigated NEs displayed toxicity for macrophages beyond the parasites. For the same nonoemulsions, a selective index (SI) greater than for Amphotericin B. Haemolytic assay using human red blood cells indicate that the NEs were less cytotoxic than amphotericin B, a widely used antifungal agent. NEs demonstrated to be an excellent strategy for increasing the penetration of these hydrophilic drugs through membranes, with a huge increase of efficacy over the sulphonamide CA inhibitor (CAI) alone.